Ultrasound surveillance is feasible after endovascular aneurysm repair - Rakemaa, Lotta (My University, 2022)
Background Surveillance after endovascular aneurysm repair (EVAR) is traditionally performed with computed tomography (CT) scans. US surveillance has been used as part of the surveillance protocol in our center since 2011. The aim of this study was to evaluate whether US can detect post-EVAR complications as well as CT. Furthermore, freedom from cancer related death was evaluated. Methods The data consisted of consecutive patients who underwent EVAR for intact abdominal aortic aneurysm (AAA) between 2000 and 2016. During 2000-2010 the surveillance protocol was based on CT (at 1, 3, and 12 months and annually thereafter; group A). Since 2011 the protocol included CT at 3 and 12 months, US at 6 months and annually thereafter; group B). If sac size increased in group B, a CT (or MRI) scan was performed. The data included reinterventions and aneurysm ruptures until December 2018. Groups were compared regarding following endpoints; secondary rupture, aneurysm-related death, aneurysm-related reintervention, and significant aneurysm diameter increase >5 mm. Results There were no significant differences in the basic characteristics or in the mean aneurysm diameter (63.5 + 9.9 mm) of the 168 patients in group A or of the 300 patients in group B. The mean clinical follow-up was 67 and 43 months and the total number of CT scans were 1.0 and 0.9 per person years in groups A and B, respectively. 40% of group B patients underwent additional CT scans. 1- and 5- year freedom from rupture preventing reintervention in group A were 94.1% (SE 1.9%) and 73.7% (SE 4.2%) and in Group B 98.1% (SE 0.8) and 81.7% (SE 3.0%) (ns.). The aneurysm ruptured in 6 patents in both groups. 1-, 5- and 8- year freedom from secondary rupture in group A was 100%, 97.9% (SE 1.5) and 96.3% (SE 2.2) and in group B 99.6% (SE 0.4), 98.0% (SE 1.3) and 96.4% (SE 2.0) (ns.). 1-, 5- and 8-year freedom from aneurysm related death was 99.4% (SE 0.6), 97.7% (SE 0.9) and 97.7% (SE 1.3) in the group A and 98.3% (SE 0.8), 97.8% (SE 0.9) and 96.2% (SE 1.8) in the group B (p=0.553) Conclusion US surveillance seemed to be safe after EVAR for intact AAA, it could detect aneurysm growth as well as CT surveillance. However, the proportion of patients in the US surveillance arm that in the end underwent additional CT scans was relatively high.
Keywords: Abdominal aneurysm, Endovascular Aneurysm Repair, Ultrasound